Comparative Analysis of Brand Equity of Internet Service Providers between Indihome and Firstmedia - Muhammad Fiqih Helmi; Rahmat Tullah; Rudi Setiyanto (JURNAL SISFOTEK GLOBAL, 2023)
The brand with high value is called brand equity. Companies must strive to build brand equity to ensure the sustainability and growth of their business and products. The problem in RT.05 Cimone is the absence of QoS data from Internet Service Providers (ISPs) Indihome and FirstMedia circulating in the area, so the public who have not installed WLAN networks cannot determine which ISP has the best quality between Indihome and FirstMedia, which may affect their daily activities such as work from home and online classes. The data collection method used in this study was reviewing various literature such as books, journals, and other bibliographical studies. The analysis showed that the building elements for ISP brand equity between Indihome and FirstMedia were better for FirstMedia than Indihome, with a QoS inequality of service parameter of 3.75 during normal hours and 4 during busy times hours, while Indihome scored 3.5 during normal hours and 3.75 during busy hours. This research aims to identify the results and values of each QoS parameter and network brand equity in ISP Indihome and FirstMedia, and indirectly, the public can determine which ISP has good quality according to their needs.